ASSESSMENT OF KNOWLEDGE, ATTITUDE, AND PRACTICE TOWARDS POST-EXPOSURE PROPHYLAXIS AMONG NURSING STUDENTS: ACROSS-SECTIONAL STUDY - Dr Muralidhar CA; Dr Rohini A; Dr.Pavithra D.P; Prof S J Vimala (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction:  Needlestick injuries (NSIs) pose a significant occupational hazard to healthcare workers (HCWs), with the potential to transmit numerous blood-borne infections, including HIV. Post-exposure prophylaxis (PEP) serves as a critical intervention to mitigate this risk. Despite various awareness programs, knowledge gaps regarding PEP, particularly among nursing professionals in India, remain a challenge. This study aimed to assess the knowledge, attitude, and practice (KAP) of nursing students toward PEP, identifying areas for improvement to enhance safety and preparedness.  Materials and Methods: A cross-sectional study was conducted among 338 nursing students using a self-administered questionnaire distributed via Google Forms. The questionnaire, structured into sections on knowledge, attitude, and practice regarding PEP, was adapted from relevant literature and pre-tested on 5% of participants. Responses were analyzed using simple percentage methods.  Results: Of the participants, 94.1% were aware of PEP, with training (46.7%) being the primary source of information. While 57.1% correctly identified NSIs as an indication for PEP, only 49.4% recognized 72 hours as the maximum window for initiating PEP, and 61.2% knew the correct duration of 28 days. Despite high awareness of PEP guidelines (92.6%), only 40.2% were familiar with their content. A majority (87%) believed PEP effectively reduces HIV transmission, yet gaps in adherence were observed. Among the 5.3% exposed to NSIs, only 27.8% were placed on PEP, with all completing the treatment. Reasons for non-adherence included fear of adverse effects and lack of information.  Conclusion: The study highlights substantial awareness of PEP among nursing students but reveals critical knowledge gaps regarding its indications, timing, and duration. Enhanced and ongoingeducational initiatives are essential to address misconceptions and promote adherence to PEP protocols. Strengthening training programs and ensuring accessible PEP guidelines can significantly improve HCWs' safety and reduce the risk of occupational HIV exposure.